2015
DOI: 10.1021/acs.jcim.5b00387
|View full text |Cite
|
Sign up to set email alerts
|

CSAR Benchmark Exercise 2013: Evaluation of Results from a Combined Computational Protein Design, Docking, and Scoring/Ranking Challenge

Abstract: Community Structure-Activity Resource (CSAR) conducted a benchmark exercise to evaluate the current computational methods for protein design, ligand docking, and scoring/ranking. The exercise consisted of three phases. The first phase required the participants to identify and rank order which designed sequences were able to bind the small molecule digoxigenin. The second phase challenged the community to select a near-native pose of digoxigenin from a set of decoy poses for two of the designed proteins. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 60 publications
0
44
0
1
Order By: Relevance
“…We participated in the 2013/14 CSAR challenge that involved rank-ordering compounds to homology models of the receptors with a given protein primary sequence, identifying close-to-native bound conformations out of a set of decoy poses, and rank-ordering the affinity of sets of congeneric compounds to a given protein. Our predictions were among the best in the field [29, 30]. We showed that the most significant contribution to a meaningful enrichment of native-like models was the identification of the best receptor structure for docking and scoring.…”
Section: Introductionmentioning
confidence: 79%
“…We participated in the 2013/14 CSAR challenge that involved rank-ordering compounds to homology models of the receptors with a given protein primary sequence, identifying close-to-native bound conformations out of a set of decoy poses, and rank-ordering the affinity of sets of congeneric compounds to a given protein. Our predictions were among the best in the field [29, 30]. We showed that the most significant contribution to a meaningful enrichment of native-like models was the identification of the best receptor structure for docking and scoring.…”
Section: Introductionmentioning
confidence: 79%
“…These datasets were primarily obtained from the pharmaceutical industry such as Abbvie 28 , Vertex 28 , and GlaxoSmithKline (GSK). A few datasets were obtained from academia, such as one from the Baker group that formed our 2013 exercise 27 . Part of the remit of the CSAR Center was to run regular exercises to actively engage the docking and scoring community in assessing the current state of the art and the impact of potential improvements.…”
Section: Introductionmentioning
confidence: 99%
“…According to the CSAR organizer’s paper 42 , our results using Vina is the 6 th among 27 predictions submitted to this phase, a larger correlation (0.819 and 0.834), while the results with the combined score and PL-PatchSurfer were among the lower ranks.…”
Section: Resultsmentioning
confidence: 93%